Understanding the impact of socioeconomic differences in breast cancer survival in England and Wales: Avoidable deaths and potential gain in expectation of life. Issue 1 (February 2015) - Rutherford, M.J.; Andersson, T.M.-L.; Møller, H.; Lambert, P.C.
Highlights Breast cancer survival varies by socioeconomic status. We examine how these differences impact on a woman's life expectancy after cancer. Women in more deprived areas lose a larger proportion of their life expectancy. Gains in life expectancy could be made by matching survival of the least deprived. Socioeconomic differences in general life expectancy also strongly influence life expectancy following cancer.